Historical dictionary of Islam - Adamec, Ludwig W. (Historical dictionaries of religions, philosophies, and movements, 2017)
This third edition of Historical Dictionary of Islam contains a chronology, an introduction, appendixes, and an extensive bibliography. It includes more than 700 cross-referenced entries on major sects, schools of theology, and jurisprudence, as well as aspects of Islamic culture.